From Mystique to Muddle: Unresolved Logic in Joko Anwar's Series - Nuswantoro, Fajar (ULTIMART Jurnal Komunikasi Visual, 2025)
Television series, as narrative mediums, rely on the audience’s ability to suspend disbelief to emotionally and intellectually engage with fictional worlds. This study examines the "Orphan" episode from Joko Anwar’s ‘Nightmares and Daydreams’, is focusing on how logical inconsistencies disrupt this process. Using Samuel Taylor Coleridge’s suspension of disbelief theory, the research explores why unanswered questions—stemming from an implausible adoption process, a child’s undisclosed peanut allergy, and an unexplained transition from a trash avalanche to a luxury house—undermine audience trust and narrative coherence. A qualitative methodology was employed, involving scene-by-scene analysis to decode messages, document arising questions, search for answers within the film, and log unresolved issues. Findings reveal that while the episode builds anticipation through mystical premises rooted in Indonesian culture, it fails to resolve key logical gaps, pushing the suspension of disbelief beyond its limits and reducing viewer engagement. The study suggests practical alternatives, such as tying adoption ease to insider ties or magical elements, to address these flaws. This analysis underscores the importance of balancing creative liberty with narrative accountability in audiovisual storytelling, offering insights for filmmakers, academics, and critics on sustaining audience immersion in the digital era. It contributes to the broader discourse on narrative quality and the application of suspension of disbelief in contemporary media. Keywords: joko anwar; suspension of disbelief; nightmare and daydream; unresolved issues